2013
DOI: 10.4253/wjge.v5.i12.600
|View full text |Cite
|
Sign up to set email alerts
|

Repeat endoscopic submucosal dissection for recurrent gastric cancers after endoscopic submucosal dissection

Abstract: AIM:To clarify the safety and efficacy of repeat endoscopic submucosal dissection (re-ESD) for locally recurrent gastric cancers after ESD. METHODS:A retrospective evaluation was performed of the therapeutic efficacy, complications and followup results from ESD treatment for early gastric cancers in 521 consecutive patients with 616 lesions at St. Luke`s International Hospital between April 2004 and November 2012. In addition, tumor size, the size of resected specimens and the operation time were compared betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 29 publications
0
4
0
1
Order By: Relevance
“…However, secondary ESD should be performed by an experienced endoscopist with precautions, including the appropriate electrosurgical knife, the appropriate dissection depth, and the careful gradual dissection of the severe fibrotic tissue along the plane of the deep submucosa or superficial proper muscle. Furthermore, the surrounding non-fibrotic tissue should first be dissected sufficiently to make a flap of the specimen and directly visualize the plane of the submucosa from the non-lifting fibrotic area to the fibrotic area[ 27 , 28 ]. Therefore, in this study, we found that the specimen size of the secondary ESD group was significantly larger than the primary ESD group.…”
Section: Discussionmentioning
confidence: 99%
“…However, secondary ESD should be performed by an experienced endoscopist with precautions, including the appropriate electrosurgical knife, the appropriate dissection depth, and the careful gradual dissection of the severe fibrotic tissue along the plane of the deep submucosa or superficial proper muscle. Furthermore, the surrounding non-fibrotic tissue should first be dissected sufficiently to make a flap of the specimen and directly visualize the plane of the submucosa from the non-lifting fibrotic area to the fibrotic area[ 27 , 28 ]. Therefore, in this study, we found that the specimen size of the secondary ESD group was significantly larger than the primary ESD group.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there were no complications in the late re-ESD group. Because locally recurrent cancers were within the mucosal layer and ESD is less invasive than gastrectomy, ESD may be considered a more suitable additional treatment for locally recurrent lesions, as suggested in previous reports 7 8 9 .…”
Section: Discussionmentioning
confidence: 89%
“…ESD is currently performed worldwide because neoplasms can be resected en bloc , and a detailed pathological assessment of resected specimens can be performed 1 2 . However, positive horizontal margins in the resected specimens are sometimes encountered after ESD 1 2 3 4 5 6 7 8 9 . Nevertheless, appropriate treatment strategies for differentiated-type gastric cancers with positive horizontal or indeterminable margins after ESD have not yet been established ( Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Occurrence of metachronous EGC lesions was observed in the ESD group only (3/14, 21.3%). Similar to previous studies, [ 33 , 34 ] the rate of metachronous GC is higher in our ESD group than the surgery group. The higher rate in the ESD group may be related to the larger remaining gastric mucosa area in the distal part of the stomach, which may have persistent helicobacter pylori infection [ 35 ] and more severe glandular atrophy or intestinal metaplasia.…”
Section: Discussionmentioning
confidence: 99%